Highly porous nitrogen-doped polyimine-based carbons with adjustable microstructures for CO2 capture - Wang, Jiacheng; Senkovska, Irena; Oschatz, Martin; Lohe, Martin R.; Borchardt, Lars; Heerwig, Andreas; Liu, Qian; Kaskel, Stefan (Journal of Materials Chemistry A, 2013)
A series of highly porous nitrogen doped porous carbons (NPCs) have been successfully prepared using a novel porous polyimine as the precursor. The resulting NPCs have a high specific surface area of up to 3195 m2 g-1, high pore volume and micropore volume (up to 1.58 and 1.38 cm3 g-1, respectively), narrow micropore size distributions, and adjustable nitrogen (1.52-5.05 wt%) depending on the activation temperatures (600-750 °C). The CO2 uptakes of the NPCs prepared at higher temperatures (700-750 °C) are lower than those prepared at milder conditions (600-650 °C). At 1 bar, NPC-650 demonstrates the best CO2 capture performance and could efficiently adsorb CO2 molecules of 3.10 mmol g-1 (136 mg g-1) and 5.26 mmol g-1 (231.3 mg g-1), at 25 and 0 °C, respectively. The NPCs also show good a initial CO2/N2 adsorption selectivity of up to 23.4 and an adsorption ratio of CO2/N 2 (6.6) at 1 bar. Meanwhile, these NPCs exhibit a high stability and facile regeneration/recyclability without evident loss of the CO2 capture capacities. © 2013 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20